2021
DOI: 10.5713/ajas.20.0215
|View full text |Cite
|
Sign up to set email alerts
|

Effects of monochromatic lights on the growth performance, carcass characteristics, eyeball development, oxidation resistance, and cecal bacteria of Pekin ducks

Abstract: Objective: Light is a significant component of housing environment in commercial poultry industry. This study was conducted to investigate whether Pekin ducks perform better under monochromatic lights than under white light with respect to their growth performance, carcass quality, eyeball development, oxidation resistance, and cecal bacterial communities.Methods: A total of 320 one-day-old male Pekin ducklings were randomly distributed into five rooms with different light treatments, white, red, yellow, green… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 30 publications
(39 reference statements)
1
4
1
Order By: Relevance
“…Duck d 35 BW and FCR were not affected by lighting treatment in the current study. These results are similar to those reported in a previous study which hypothesized duck performance may not be affected by colored LEDs at low light intensities such as the 5 lux used in the reported study and the 5 gallilux used in the current study ( Hua et al., 2021 ). Two other reports indicating differences in duck BW maintained a light intensity of 20 lux ( Hassan et al., 2017 ) and 25 lux ( Campbell et al., 2015 ) respectively.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Duck d 35 BW and FCR were not affected by lighting treatment in the current study. These results are similar to those reported in a previous study which hypothesized duck performance may not be affected by colored LEDs at low light intensities such as the 5 lux used in the reported study and the 5 gallilux used in the current study ( Hua et al., 2021 ). Two other reports indicating differences in duck BW maintained a light intensity of 20 lux ( Hassan et al., 2017 ) and 25 lux ( Campbell et al., 2015 ) respectively.…”
Section: Discussionsupporting
confidence: 92%
“…In the current investigation, eye weight was greater in WHITE and GREEN ducks than in RED and BLUE ducks. These results are not aligned with Hua et al. (2021) , which reported increased eyeball length (front-to-back) and width (side-to-side) in ducks reared under longer wavelengths such as yellow, red, and green light compared to blue light, and eye weight was not affected.…”
Section: Discussioncontrasting
confidence: 84%
See 1 more Smart Citation
“…Meanwhile, Hassan et al (2016) reported higher body weights for ducks raised in blue and green than yellow and white light. Other studies have found no relationship between bodyweights and light color ( Hua et al, 2021 ; House et al, 2021b ). Results regarding the feed conversion ratio ( FCR ) of ducks housed under different light colors have been equally conflicting, with two studies finding no differences ( Hassan et al, 2016 ; House et al, 2021b ) and another reporting improved FCR for ducks housed under blue and green light vs. other colors ( Kim et al, 2014 ).…”
Section: Duck Welfare In Relation To the Housing Environmentmentioning
confidence: 89%
“…However, the effect of different light wavelengths on the intestinal microbiome composition is also related to species and the location of the digestive tract. In Peking ducks, when imposing low-light intensity blue or green monochromatic light, the amount of Firmicutes increased but the amount of Bacteroidetes decreased in the cecum, compared to white light [ 32 ].…”
Section: Discussionmentioning
confidence: 99%